Pregunta
upstudy study bank question image url

Wo angies in an equilateral triangie are \( (a+b) \) and \( (2 a-10 b) \) degrees Find the values of \( a \) and \( b \).

Ask by Bird Daniel. in Papua New Guinea
Feb 03,2025

Solución de tutoría real

Respuesta verificada por el tutor

Responder

\( a = 55^\circ \) and \( b = 5^\circ \).

Solución

To solve for \( a \) and \( b \) in an equilateral triangle where the angles are given by \( (a + b) \) and \( (2a - 10b) \) degrees, follow these steps: 1. **Understanding an Equilateral Triangle:** - In an **equilateral triangle**, all three angles are equal. - Each angle in an equilateral triangle is **60 degrees**. 2. **Setting Up the Equations:** - Since all angles are equal, we can set: \[ a + b = 60^\circ \] \[ 2a - 10b = 60^\circ \] 3. **Solving the Equations:** - From the first equation: \[ a = 60^\circ - b \] - Substitute \( a \) from the first equation into the second equation: \[ 2(60 - b) - 10b = 60 \] \[ 120 - 2b - 10b = 60 \] \[ 120 - 12b = 60 \] \[ -12b = -60 \] \[ b = 5^\circ \] - Substitute \( b = 5^\circ \) back into the first equation to find \( a \): \[ a = 60^\circ - 5^\circ = 55^\circ \] 4. **Final Solution:** \[ a = 55^\circ \quad \text{and} \quad b = 5^\circ \] **Answer:** After simplifying, a is 55 degrees and b is 5 degrees.

Revisado y aprobado por el equipo de tutoría de UpStudy

error msg
Explicar
Simplifique esta solución

Bonus Knowledge

In an equilateral triangle, all angles are equal and sum up to \( 180 \) degrees. This means if two angles are \( (a+b) \) and \( (2a-10b) \), we can set up the equation: \[ (a + b) + (2a - 10b) + x = 180 \] Where \( x \) is the third angle which is also equal to \( (a + b) \) since all angles in an equilateral triangle are the same. Therefore, we have: \[ (a + b) + (2a - 10b) + (a + b) = 180 \] Combining the terms, we get: \[ 4a - 8b = 180 \] To simplify, divide the entire equation by 4: \[ a - 2b = 45 \] Now we have one equation. Since \( a + b \) should also equal the third angle, we know: \[ a + b = 60 \] Now we have two equations: 1. \( a - 2b = 45 \) 2. \( a + b = 60 \) We can solve these equations. From the second equation, we can express \( a \): \[ a = 60 - b \] Substituting \( a \) into the first equation: \[ (60 - b) - 2b = 45 \] Simplifying this gives: \[ 60 - 3b = 45 \] Now, isolating \( b \): \[ 3b = 15 \\ b = 5 \] Now substitute \( b = 5 \) back into the equation for \( a \): \[ a + 5 = 60 \\ a = 55 \] Thus, the values of \( a \) and \( b \) are: \[ a = 55, \quad b = 5 \]

preguntas relacionadas

Latest Geometry Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad